Identification of morphological and molecular markers for yield and fertility in single spore isolates of Agaricus bisporus - Kamal, Shwet; Singh, Manjit (Mushroom Research, 2012)
Breeding in Agaricus bisporus is cumbersome due to its secondary homothallic nature and needs morphological and molecular markers for yield and fertility. Sixty-nine fertile isolates representing four strains were screened for radial growth on malt extract agar (MEA), downward linear growth on compost and yield. There was no significant correlation of yield with radial growth on MEA (r = 0.12) suggesting that the growth on MEA in Petri plates cannot be an indicator of yield performance of the genotype. The downward linear growth on compost, however, showed highly significant relationship with yield (r = 0.77; y = 0.33x 10.01; R = 0.53) suggesting that downward mycelial growth on compost can be used to reject the low yielding isolates. RAPD and 5.8S rDNA sequencing showed low polymorphism among the isolates, but could partly distinguish fertile and non-fertile isolates. On the other hand ISSR markers showed high polymorphism among fertile (30%) and non-fertile isolates (66%) and also separated fertile and non-fertile isolates..